Occlusion and coupling effects with different earmold designs – all a matter of opening the ear canal?. (1st March 2023) - Denk, Florian; Hieke, Thomas; Roberz, Malte; Husstedt, Hendrik
Abstract: Objective: Ear canal occlusion by a hearing aid leads to an unnatural sound of the own voice due to a level increase of bone-conducted low-frequency components of the ear canal. Opening the ear through vents or domes reduces this so-called occlusion effect, however at the cost of reduced hearing aid performance. For individual earmolds, several other design options to reduce the occlusion effect have been proposed but not reliably evaluated. Design: The occlusion effect and coupling parameters were assessed through subjective ratings and real-ear measurements. Study sample: Six individual earmold designs, each with different venting options, were tested in 10 subjects. Results: In line with previous studies, our data show that the opening of the ear as described by the acoustic mass of the vent is the prime parameter that predicts both the occlusion effect and coupling parameters. However, the design of the earmold, most importantly the location where sealing of the ear canal is achieved, is another important factor for occlusion and coupling effects. Conclusions: Although no reduction of the occlusion effect seems possible without additional opening of the ear canal, some earmold modifications seem to aggravate the occlusion effect as compared to a standard earmold with equivalent vent.